Provision of information by midwives for pregnant women in England on guidance on foods/drinks to avoid or limit - Lucy Beasant; Jenny Ingram; Rachel Tonks; Caroline M. Taylor (BMC, 2023)
Abstract Background The National Health Service (NHS) website gives guidance for pregnant women in England on foods/drinks to avoid or limit because of microbiological, toxicological or teratogenic hazards. These include, for example, some types of soft cheeses, fish/seafood and meat products. This website and midwives are trusted sources of information for pregnant women, but the ways in which midwives can be supported to provide clear and accurate information are unknown. Aims The aims were to: (1) determine midwives' accuracy of recall of information and confidence in delivering the guidance to women; (2) identify barriers to provision; (3) identify the ways in which midwives provide this information to women. Methods Registered Midwives practicing in England completed an online questionnaire. Questions included those on what information they provided and their confidence in delivering it, the ways they provided information on foods to avoid/limit, their recall of some of the guidance, and what resources they used. Ethics approval was given by the University of Bristol. Results More than 10% of midwives (n = 122) were 'Not at all confident/Don't know' in providing advice about ten items, including game meat/gamebirds (42% and 43%, respectively), herbal teas (14%) and cured meats (12%). Only 32% correctly recalled overall advice on eating fish, and only 38% the advice on tinned tuna. The main barriers to provision were lack of time in appointments and lack of training. The most usual methods of disseminating information were verbal (79%) and signposting to websites (55%). Conclusion Midwives were often unconfident about their ability to provide accurate guidance, and recall on items tested was frequently mistaken. Delivery of guidance by midwives on foods to avoid or limit needs to be supported by appropriate training and access to resources, and sufficient time in appointments. Further research on barriers to the delivery and implementation of the NHS guidance is needed.